PELAKSANAAN ASESMEN TERHADAP PECANDU NARKOTIKA OLEH SATUAN RESERSE NARKOBA KEPOLISIAN RESOR KEPULAUAN MENTAWAI - Irmon, Irmon; Faniyah, Iyah (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
The government's effort to tackle the problem of narcotics abuse is to enact Law No. 35 of 2009 concerning Narcotics. In its development to protect addicts and victims of narcotics abuse, it no longer boils down to imprisonment sanctions, but empties into rehabilitation as stipulated in SEMA Number 4 of 2010 and SEMA Number 11 of 2011. As for rehabilitation, every addict and victim of narcotics abuse must an assessment process was carried out by the Integrated Assessment Team. The Assessment Process is the initial process where narcotics addicts and victims of narcotics abuse report to the Police and Obligatory Report Receiving Agencies (IPWL), as Satresnarkoba Polres Mentawai did which conducted four assessments during 2015 to 2017